Parent Praise to 1‐ to 3‐Year‐Olds Predicts Children's Motivational Frameworks 5 Years Later. Issue 5 (11th February 2013) - Gunderson, Elizabeth A.; Gripshover, Sarah J.; Romero, Carissa; Dweck, Carol S.; Goldin‐Meadow, Susan; Levine, Susan C.
Abstract : In laboratory studies, praising children's effort encourages them to adopt incremental motivational frameworks—they believe ability is malleable, attribute success to hard work, enjoy challenges, and generate strategies for improvement. In contrast, praising children's inherent abilities encourages them to adopt fixed‐ability frameworks. Does the praise parents spontaneously give children at home show the same effects? Although parents' early praise of inherent characteristics was not associated with children's later fixed‐ability frameworks, parents' praise of children's effort at 14–38 months ( N = 53) did predict incremental frameworks at 7–8 years, suggesting that causal mechanisms identified in experimental work may be operating in home environments.